2001
DOI: 10.1046/j.1464-5491.2001.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Audit of influenza and pneumococcal vaccination uptake in diabetic patients attending secondary care in the Northern Region

Abstract: Vaccination rates in these diabetic patients are unsatisfactory. Secondary care health professionals might increase rates by raising the topic in consultations. Diabet. Med. 18, 599-603 (2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
(22 reference statements)
6
19
0
Order By: Relevance
“…Families declare that "too much vaccination" is performed on their children, that these cause the immune system to attenuate and influenza vaccine even "causes" the disease itself (25). In adult diabetics, fear of adverse-effects is among the least common reasons but it increases to be more common in children (29)(30)(31). The rates of fear of adverse-effects are between 8.9-18.8% in different studies (11,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Families declare that "too much vaccination" is performed on their children, that these cause the immune system to attenuate and influenza vaccine even "causes" the disease itself (25). In adult diabetics, fear of adverse-effects is among the least common reasons but it increases to be more common in children (29)(30)(31). The rates of fear of adverse-effects are between 8.9-18.8% in different studies (11,21).…”
Section: Discussionmentioning
confidence: 99%
“…This reason is most common in adult diabetics and vaccine refusal rate because this reason rises to 55% (2,13,27,29,30). Daley et al (13) showed that, among the non-receivers, about 33% of the families of children with chronic illnesses did not receive the influenza vaccine because they did not believe in its usefulness.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic patients are particularly susceptible to influenza and pneumococcal infection, and are at increased risk for morbidity and mortality from them [1]. Although the necessity of influenza and pneumococcal immunization in diabetic patients is widely accepted [2], vaccination rates are unsatisfactory [3,4]. Our aim was to estimate the prevalence of influenza and pneumococcal vaccination among diabetic patients attending primary care, in Greece.…”
Section: Prevalence and Adjusted Odds Ratio (Or) By Variables Of Thementioning
confidence: 99%
“…To avoid underreporting, the information was confirmed by checking the patient's prescription health booklet. Additional data were collected using a standardized questionnaire [3].…”
Section: Prevalence and Adjusted Odds Ratio (Or) By Variables Of Thementioning
confidence: 99%
“…A comprehensive standardized questionnaire designed to evaluate the vaccination status of diabetes mellitus patients by Wahid et al was used (8). Our data collected by direct questioning included age, gender, marital status, occupation, level of education, family's monthly income and presence of chronic diseases.…”
Section: Questionnairementioning
confidence: 99%